Influence of Game Design and Playability Toward Continuance Intention Using TAM Framework - Rocky Tarsisius Pantouw; Daniel Tumpal H Aruan (IPTEK Journal of Proceedings Series, 2019)
As the growth of game industry, only few Studies in mobile games, and also focused on pre-adopting while ignoring post adoption behaviors. One intrinsic factor considered affecting gameplay is enjoyment. Some research has already conducted to understand what is enjoyment driver. Enjoyment is an external factor that influenced perceived usefulness. where perceived of usefulness is variable proposed in TAM. This study aims to examine impact the game design attribute that fit and influence enjoyment while play game and as a motive of continuance mobile game use in MOBA genre. This research adopts game design attributes of challenge, variety, novelty, design aesthetics, social interaction, playability attributes consist of perceived of use and interactivity. Structural Equation Modeling (SEM) is used for data analysis. The model is tested with 206 actual users. The findings put Novelty, design aesthetic and interactivity under observed. This research concluded that continual mobile game use is strongly driven by perceived of usefulness. The implications are discussed in the paper